Perbedaan Reaksi Pasar pada Perusahaan Pemenang Indonesia Sustainability Reporting Award (Isra) ( Studi Kasus pada Perusahaan Pemenang ISRA periode 2009-2011) - Randika Bagus Linuwih; Yeterina Widi Nugrahanti (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2016)
ABSTRACTThe purpose of this study is to examine the change ofmarket reaction arround the date of Indonesia Sustainability Reporting Award (ISRA announcement. The market reaction is measured byabnormal return dan trading volume activity.The sample of the study consist of 25 companies listed on the Indonesian Stock Exchange which accept the appreciation of ISRA in 2009-2011. Data that used in this study consist of share’s daily closing priceand daily trading volume. The estimation period is 30 days and event period is 11 days by using Market Models. Technique of analyzed for examining the hypothesis is Wilcoxon Sign Test at level significant of 10%.The results of this research show that ISRAannouncementdid not get any response from the investors, because there were no significant changes to the abnormal return before and after the announcement.The examination of trading volume activity proves that there are any significant differences in trading volume activity especially on fifth day and second day before the announcement, and the first day and second day after ISRA 2009-2011 announcement.